1986
DOI: 10.1111/j.1432-1033.1986.tb09611.x
|View full text |Cite
|
Sign up to set email alerts
|

Separation and identification of the major constituents of cytoplasmic gels from macrophages

Abstract: Proteins which bind to actin filaments in macrophages were investigated by developing a procedure for the isolation of cytoplasmic gels. The gels were found to consist of five major constituents: actin, filamin and the 105-kDa, 70-kDa and 55-kDa components. Prolonged exposure of this macromolecular complex to high-ionicstrength buffer solubilized almost all the proteins, leaving behind the 55-kDa component along with a large amount of actin. Gel filtration of the solubilized extract led to the isolation of fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 56 publications
(8 reference statements)
1
21
0
Order By: Relevance
“…It is generally considered that the gel-sol transformation of actin is mediated by actinassociated proteins. Several kinds of actin-associated proteins such as gelsolin Yin et al, 19811, a-actinin (Bennett et al, 19841, actinbinding protein (Hartwig and Stossel, 19751, and actinbundling protein (Pacaud, 1986;Pacaud and Harricane, 1987) were isolated from the cytoplasm of macrophages and characterized. Some of these actinassociated proteins were considered t o be involved in the gel-sol transformation of actin in the cytoplasm of macrophages (Hartwig and Stossel, 1975;Pacaud, Fig.…”
Section: In Situ Morphological Relationship Of Cytoskeletal Elements mentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally considered that the gel-sol transformation of actin is mediated by actinassociated proteins. Several kinds of actin-associated proteins such as gelsolin Yin et al, 19811, a-actinin (Bennett et al, 19841, actinbinding protein (Hartwig and Stossel, 19751, and actinbundling protein (Pacaud, 1986;Pacaud and Harricane, 1987) were isolated from the cytoplasm of macrophages and characterized. Some of these actinassociated proteins were considered t o be involved in the gel-sol transformation of actin in the cytoplasm of macrophages (Hartwig and Stossel, 1975;Pacaud, Fig.…”
Section: In Situ Morphological Relationship Of Cytoskeletal Elements mentioning
confidence: 99%
“…The interaction of actin with actin-associated proteins was reported to be sensitive to intracellular calcium ions, which are a second messenger on many cell functions (Bennett et al, 1984;Pacaud, 1986;Pacaud and Harricane, 1987;Stossel et al, 1985;. Since the intracellular concentration of calcium ion was connected with the ligand-receptor interaction and endocytosis (Young et al, 19841, the change of calcium ion concentration at micromolar level might play a role as a signal for regulation of the lysosomal movement following endocytosis during heterophagy.…”
Section: In Situ Morphological Relationship Of Cytoskeletal Elements mentioning
confidence: 99%
“…Furthermore, there is some evidence indicating that lysosomal membranes in polymorphonuclear leukocytes contain intramembranous particles (14) and glycoproteins associated with their membranes (16). The interaction of actin with actin-associated proteins was reported to be sensitive to intracellular calcium ion which is a second messenger in cell functions (4,17,18,22,31,32). It was reported that the ligand-receptor interaction increased the concentration of intracellular calcium ion, and increasing calcium ion in cytoplasm might play a role of the signals for endocytic process (33).…”
Section: Discussionmentioning
confidence: 99%
“…Several kinds of actinassociated proteins were isolated from nonmuscle cells (22). Actin-associated proteins such as gelsolin (31), a-actinin (4), actin-binding protein (10) and actin-bundling protein (17,18) were isolated from the cytoplasm of macrophages. These actinassociated proteins are thought to be involved in the gel-sol transformation of actin in the cytoplasm of macrophages (10, 17, 18, 22-24, 31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…The macrophage protein was shown to bind to polymerized actin in a calcium-dependent manner (13,14). Also, Matsushima and co-workers (12) have purified L-plastin from human macrophages (identified as L-plastin by sequence [8]) and have demonstrated that it is phosphorylated at serine residues.…”
mentioning
confidence: 99%